Evaluation of Nonmotor Symptoms in Diagnosis of Parkinsonism and Tremor - Andrew H. Evans; Chiun-Hian Chai (Parkinson's Disease)
Background. Nonmotor symptoms particularly olfactory dysfunction, RBD, depression, hallucinations, and constipation are currently not included in the typical clinical criteria for diagnosing Lewy body Parkinsonian disorders (LBPD). The aim of this study is to determine the diagnostic value of nonmotor symptoms in patients presenting with Parkinsonism and tremor. Methods. All new patients seen between January 2007 and May 2013 in the Movement Disorders Specialist Clinics of the Royal Melbourne Hospital (RMH), who were referred with a possible neurodegenerative syndrome or concerns of Parkinsonism and/or tremor, were included. Patients underwent routine evaluation with the four-minute “Sniffin Sticks” test, RBD, depression, and constipation. Results. 291 patients were included in the analysis. Conclusion. We found that lower olfaction scores based on “Sniffin Sticks” testing combined with reports of depression and constipation are independent predictors for the diagnosis of the spectrum of Lewy body Parkinsonian disorders (LBPD). Parkinson’s disease (PD) cannot be reliably clinically differentiated from other causes of Parkinsonism that share symptomatology and structural abnormalities.